28th Symposium on Microelectronics Technology and Devices (SBMicro 2013) 2013
DOI: 10.1109/sbmicro.2013.6676181
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic magnetoconductance effects in strained FETs

Abstract: We introduce ex p erimental, modeling and simulation results of the electrical p erformance of 28nm FETs, operated under the action of an external magnetic field B. Negative resistance and magneto-current am p lification are some of the effects discussed through this research com p ilation done within the Microelectronics research

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Experiments in some case studies have shown that magnetic fields cause a current deflection in the drain current voltage, which alters the conductivity of the active region resulting in asymmetric magnetic tunneling and non-uniform spatial conduction in MOSFETs [11], [12]. Wick made the first measurement of the Hall-effect of silicon on a fairly impure sample [13].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments in some case studies have shown that magnetic fields cause a current deflection in the drain current voltage, which alters the conductivity of the active region resulting in asymmetric magnetic tunneling and non-uniform spatial conduction in MOSFETs [11], [12]. Wick made the first measurement of the Hall-effect of silicon on a fairly impure sample [13].…”
Section: Introductionmentioning
confidence: 99%
“…This leads to complicated various short channel effects (SCE) such as the effect of hot carriers effect, threshold voltage Indonesian J Elec Eng & Comp Sci ISSN: 2502-4752  roll-off, substrate carrier effect, higher change in hall voltage and drain-source resistance (RDS) in the linear region [8], [13], [15], [16]. Experimental of several case studies indicate that the magnetic field induced current deflection on the drain-current voltage and changing the conductivity of the active region [17], induces asymmetrical magneto tunneling conductance in MOSFETs resulting of non-homogeneous space mechanical strain [18], [19]. The magneto-transconductance of N-type metal-oxide-semiconductor (N-MOS) transistors exposed to the external magnetic field B=7T and 14T is reduced by 7% and 28% respectively due to the current reduction that comes from the deflection of the current lines inside the channel consequently of the Lorentz force acting to the current [14], [20].…”
Section: Introductionmentioning
confidence: 99%